Women in cancer profile: A gender agenda? - Bevan,C (Endocrine-Related Cancer, 2016)
Extract: Growing up, I never understood why so many people professed to have no interest in science. How could understanding how things work not be the most fascinating thing? And how we, as organisms, develop and function (or fail to) seemed to me the most fascinating thing of all. One of my most inspiring school teachers was the head of Biology and 6th-form, Dr Chris Haworth, who undertook to nurture my ambition to gain a place at "Oxbridge" (no-one from our comprehensive school in the far north of England had previously gone to either Cambridge or Oxford). I remember one lesson we came in to find dandelion leaves strewn around the room. It turned out they were all different, representing a fair proportion of the 250-odd species of dandelion on which, had I but appreciated it at the time, Dr Haworth was a recognised authority. While many of my classmates flatly refused to see any difference between the leaves, it was my first introduction to genetic diversity. And speaking of diversity, I wanted to keep my options open so crammed in as many A level subjects as I could, from Applied Mathematics to English Literature, refusing to drop any despite the recommendations by careers advisers and admissions tutors ...